Citizen-led digital policing and democratic norms: The case of self-styled paedophile hunters. (September 2021) - Hadjimatheou, Katerina
Citizen involvement in the provision of security is often presented as a win–win way to relieve pressure on police resources while building stronger, more responsible and democratically engaged communities. Governments in countries such as the United Kingdom and the Netherlands have adopted a 'strategy of responsibilisation' designed to encourage, enable and support citizens to take on tasks otherwise left for police. Yet, this strategy conspicuously ignores the growing number of citizen-led digital policing initiatives which operate independently without the encouragement or guidance of police. This article considers the implications of this trend for democratic norms in policing. It uses the phenomenon of self-styled paedophile hunters – which are now active in countries around the world – as a case study. The article makes comparisons between such initiatives and other, relatively well-theorised informal security providers, such as vigilante groups and civilian policing. It argues that, like vigilantes, citizen-led digital police often challenge democratic principles of transparency, accountability and the rule of law. Yet, like other civilian policing initiatives, they increase empowerment and participation, and rely for their success on the presence of strong and legitimate institutions of justice, to which they ultimately defer. These characteristics present a discreet set of opportunities and challenges for contemporary policing, which this article argues can only be addressed by strategic police engagement.